KARAKTERISTIK SENSORI DAN SIFAT KIMIA MI KERING DENGAN PENAMBAHAN TEPUNG BONGGOL PISANG (Mussa paradisiaca L.) DAN TEPUNG WORTEL (Daucus carota L.) SENSORY CHARACTERISTICS AND CHEMICAL PROPERTIES OF DRY NOODELS WITH THE ADDITION OF BANANA HUMP FLOUR (Mussa paradisiaca L.) AND CARROT FLOUR (Daucus carota L.) - Susilawati, Susilawati; Indraningtyas, Lathifa; Sartika, Dewi; Hanifah, Hanifah (Jurnal Agroindustri Berkelanjutan, 2024)
Dry noodles are made from wheat flour which comes from wheat flour imported from abroad and causes people to become dependent on wheat flour. Then the banana and carrot humps are processed into flour which is rich in nutrition and good for health and can be used as an alternative to the use of wheat flour. The aim of the research was to obtain a formulation of kepok banana hump flour and carrot flour which produces dry noodles with the best sensory characteristics and chemical properties according to SNI 8217:2015. This study was arranged in a Complete Randomized Block Design (RAKL) with six treatments and four replications. Comparison of banana cob flour and carrot flour consisted of six levels, namely D1 (25%:0%), D2 (20%:5%), D3 (15%:10%), D4 (10%:15%), D5 (5%:20%), D6 (0%:25%). The data obtained were analyzed for variance and further tested with the Least Significant Difference (LSD) test at the 5% level. The results showed that dry noodles with the addition of 5% banana cob flour and 20% carrot flour (D5) produced color with a score of 4,000 (likes), texture with a score of 4,067 (likes), aroma with a score of 3,733 (likes), taste with a score of 3,675 (likes), and overall acceptability with a score of 3,923(likes), water content of 6,033% (bb), ash content of 3,31% (bb), carbohydrate content 54.26% (bb) and 4.89% (bb) crude fiber content meet the Indonesian national standard for dry noodles (SNI 8217: 2015).